Cytosolic aconitase activity sustains adipogenic capacity of adipose tissue connecting iron metabolism and adipogenesis. Issue 4 (30th December 2014) - Moreno, María; Ortega, Francisco; Xifra, Gemma; Ricart, Wifredo; Fernández‐Real, José Manuel; Moreno‐Navarrete, José María
Abstract : To gain insight into the regulation of intracellular iron homeostasis in adipose tissue, we investigated the role of iron regulatory protein 1/cytosolic aconitase 1 (ACO1). ACO1 gene expression and activity increased in parallel to expression of adipogenic genes during differentiation of both murine 3T3‐L1 cells and human preadipocytes. Lentiviral knockdown (KD) of Aco1 in 3T3‐L1 preadipocytes led to diminished cytosolic aconitase activity and isocitrate dehydrogenase 1 (NADP + ), soluble (Idh1) mRNA levels, decreased intracellular NADPH:NADP ratio, and impaired adipogenesis during adipocyte differentiation. In addition, Aco1 KD in fully differentiated 3T3‐L1 adipocytes decreased lipogenic, Idh1, Adipoq, and Glut4 gene expression. A bidirectional cross‐talk was found between intracellular iron levels and ACO1 gene expression and protein activity. Although iron in excess, known to increase reactive oxygen species production, and iron depletion both resulted in decreased ACO1 mRNA levels and activity, Aco1 KD led to reduced gene expression of transferrin receptor (Tfrc) and transferrin, disrupting intracellular iron uptake. In agreement with these findings, in 2 human independent cohorts ( n = 85 and n = 38), ACO1 gene expression was positively associated with adipogenic markers in subcutaneous and visceral adipose tissue. ACO1 gene expression was also positively associated with the gene expression of TFRC while negatively linked to ferroportin (solute carrier family 40 (iron‐regulated transporter), member 1) mRNA levels. Altogether, these results suggest that ACO1 activity is required for the normal adipogenic capacity of adipose tissue by connecting iron, energy metabolism, and adipogenesis.—Moreno, M., Ortega, F., Xifra, G., Ricart, W., Fernández‐Real, J. M., Moreno‐Navarrete, J. M. Cytosolic aconitase activity sustains adipogenic capacity of adipose tissue connecting iron metabolism and adipogenesis. FASEB J. 29, 1529‐1539 (2015). www.fasebj.org